2017
DOI: 10.1007/s11250-017-1293-9
|View full text |Cite
|
Sign up to set email alerts
|

Growth performance of broilers fed on sprouted-roasted guar bean (Cyamopsis tetragonoloba) based diets

Abstract: In a completely randomized block design with 96 Cobb-500 broilers, a study was conducted to evaluate the potential of dietary inclusion of sprouted then roasted guar bean in broiler diets. The 96 male day-old broiler chicks, blocked by pen into equal weight groups of six chicks replicated four times per treatment, were randomly allocated to treatment diets containing graded levels of sprouted then roasted guar bean meal (GBM) at 0, 50, 100 and 150 g kg inclusion level. The guar bean was sprouted and roasted to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Results from this study showed that a significant quadratic trend was observed for NDFD in response to increasing dietary levels of SWM, which indicates that the presence of polysaccharides (fucoidan, laminarin, alginate, and cellulose) in the seaweed [ 18 , 19 ] may reduce its utilisation at higher inclusion rates. Indeed, non-starch polysaccharides such as cellulose, pectins, arabinoxylans, and β -glucans are known to suppress nutrient digestibility in poultry [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Results from this study showed that a significant quadratic trend was observed for NDFD in response to increasing dietary levels of SWM, which indicates that the presence of polysaccharides (fucoidan, laminarin, alginate, and cellulose) in the seaweed [ 18 , 19 ] may reduce its utilisation at higher inclusion rates. Indeed, non-starch polysaccharides such as cellulose, pectins, arabinoxylans, and β -glucans are known to suppress nutrient digestibility in poultry [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, replacing SBM with GM in broiler diets at levels of 3-18% at different growth stages, showed an improvement in growth performances and carcass parameters at lower levels of 3-9 % (Gheisari et al, 2011). Another study revealed optimum inclusion level at 50 g/ kg of sprouted guar than roasted guar bean meal suggested beneficial for growth in broiler diets (Madzimure et al, 2017). A study of Janampet et al (2016) confirmed that the inclusion of 50% guar meal instead of groundnut cake enhanced the growth rate and digestion coefficient of nutrients without any adverse effects on performance.…”
Section: Growth Performance and Carcass Characteristicsmentioning
confidence: 94%
“…As chickens decrease feed intake, their nutrient intake also decreases resulting in lighter weight. Anti-nutritional factors found in T. esculentum are known to suppress nutrient digestibility in chickens (Madzimure et al, 2017). In addition, Jackson et al (2010) reported T. esculentum (Burchell) to be a potential source of phytonutrients including phenolic compounds such as tannin, trypsin inhibitor, phytate and oligosaccharides.…”
Section: Discussionmentioning
confidence: 99%